Temporal adaptation strategies for spatio-temporal image alignment in inter-sequence error concealment of digital TV - Tröger, Tobias; Kaup, André (2011 18th IEEE International Conference on Image Processing, ICIP 2011, 2011)
In multi-broadcast scenarios, inter-sequence error concealment replaces lost image blocks of digital TV signals with error-free ones of low-resolution reference signals. Although single reference frames are misaligned spatio-temporally, the reconstruction quality is significantly higher than for conventional techniques. However, it can be further increased by reusing the alignment parameters of previous frames in case of misalignment of the current frame. Two strategies are proposed for this temporal adaptation of the alignment parameters either minimizing the additional complexity or maximizing the reconstruction quality. Overall, a gain of up to 5.0 dB PSNR Y is obtained while the computation time does not rise by more than 1.8%. © 2011 IEE